A COMPUTATIONAL APPROACH TO TEACHING LIGHT VERB CONSTRUCTIONS: FROM ITALIAN TO ENGLISH, FRENCH, AND ROMANIAN (Theoretical and Applied Linguistics@ro, 2025)
This paper presents a computational approach to the teaching of Light Verb Constructions (LVCs) from a contrastive perspective, within the framework of a multilingual digital project directed by Sabine E. Koesters Gensini. The project targets university-level learners and involves eight third languages (L3) – Albanian, Dutch, French, German, Romanian, Russian, Spanish, and Swedish – with Italian (L1) and English (L2) serving as starting points for the exploration of LVCs in the L3. Focusing on Italian, English, French, and Romanian, the article outlines the project’s theoretical and practical framework, with an emphasis on the semantic and morphosyntactic properties of LVCs, investigated within a contrastive analytical perspective. After outlining the criteria used to design a digital software tool for language teaching, illustrating how LVCs can be effectively taught through a computational, data-driven approach, the study offers a detailed analysis focused on the properties of verbo-nominal constructions with the Italian light verb fare (to do/make). Finally, drawing on authentic learner data in Romanian, this article highlights recurring error patterns in LVCs acquisition and argues for the systematic integration of these structures into foreign language curricula in the university context.
Keywords: light verb constructions; L2/L3 acquisition; e-learning; applied linguistics; language teaching